The Concept of Islamic Education According to Imam Al-Ghazali and Its Relevance to Contemporary Education: A Literature Analysis Study - Mohammad Nasrun (PT. Berkah Smart Academica, 2025)
This literature analysis study examines the educational philosophy of Imam Al-Ghazali, a prominent Islamic scholar, and its relevance to contemporary education. The study explores Al-Ghazali's core principles of Islamic education, including the integration of religious and secular knowledge, the importance of moral and spiritual development, and the cultivation of critical thinking. The methodology involves a comprehensive review of Al-Ghazali's works, particularly his seminal work,